Hard Times and New Deal in Kentucky : 1929-1939 - Blakey, George T. (Book collections on Project MUSE., 1986)
The Great Depression and the New Deal touched the lives of almost every Kentuckian during the 1930s. Fifty years later the Commonwealth is still affected by the legacies of that era and the policies of the Roosevelt administration. George T. Blakey has written the first full study of this turbulent decade in Kentucky, and he offers a fresh perspective on the New Deal programs by viewing them from the local and state level rather than from Washington. Thousands of Kentuckians worked for New Deal programs such as the Civilian Conservation Corps and the Works Projects Administration; thousands mor.